New approaches to controlling an outbreak of chickenpox in a large immigration detention setting in England: the role of serological testing and mathematical modelling. (2020) - Zhang, Xu-Sheng; Smith, Alexandra; Patel, Bharat; Anderson, Charlotte; Pomeroy, Laura; Higgins, Gillian; O'Moore, Éamonn; Chow, Yimmy; Atchison, Christina
Abstract: Chickenpox is caused by varicella-zoster-virus (VZV) and is highly contagious. Immigration detention settings are a high-risk environment for primary VZV transmission, with large, rapidly-changing populations in close quarters, and higher susceptibility among non-UK-born individuals. During outbreaks, operational challenges occur in detention settings because of high-turnover and the potential need to implement population movement restriction for prolonged periods. Between December 2017 and February 2018, four cases of chickenpox were notified amongst 799 detainees in an immigration removal centre (IRC). Microbiological investigations included case confirmation by vesicular fluid polymerase chain reaction, and VZV serology for susceptibility testing. Control measures involved movement restrictions, isolation of cases, quarantining and cohorting of non-immune contacts and extending VZV immunity testing to the wider detainee population to support outbreak management. Immunity was tested for 301/532 (57%) detainees, of whom 24 (8%) were non-immune. The level of non-immunity was lower than expected based on the existing literature on VZV seroprevalence in detained populations in England. Serology results identified non-immune contacts who could be cohorted and, due to the lack of isolation capacity, allowed the placement of cases with immune detainees. The widespread immunity testing of all detainees was proving challenging to sustain because it required significant resources and was having a severe impact on operational capacity and the ability to maintain core business activities at the IRC. Therefore, mathematical modelling was used to assess the impact of scaling back mass immunity testing. Modelling demonstrated that interrupting testing posed a risk of one additional case compared to continuing with testing. As such, the decision was made to stop testing, and the outbreak was successfully controlled without excessive strain on resources. Operational challenges generated learning for future outbreaks, with implications for a local and national policy on IRC staff occupational health requirements, and proposed reception screening of detainees for VZV immunity.